노인장기요양보험제도에 관한 치과위생사의 인지도 - 김지현; Ji Hyun Kim; 황지민; Ji Min Hwang; 박용덕; Young Duk Park (Chiwisaeng gwahakoeji, 2010)
The purpose of this study is to cover dental hygienists who work for metropolitan dental hospitals or clinics in Seoul city, Incheon city and Gyeonggi province from January to April 2009 and profile their awareness of Long-term Senior Care Insurance System (hereinafter called 'LSCI (System)', so that it may provide material reference data to contribute to expanding and establishing oral health medical services in the framework of LSCI System. As a result, this study could come to the following conclusions: 1. It was found that the highest priority of dental hygienists' visiting oral hygienic services under LSCI System was focused on 'caring and preventive treatment', and their secondary priority was focused upon 'oral health education.' 2. In response to a question item about whether dental hygienists need dentist's prescription in written before performing their visiting oral hygienic services, it was found that 38.2% dental hygienists answered 'Yes (necessary)' and 61.8% answered 'No (unnecessary).' 3. In response to a question item about whether dental hygienists may open up long-term senior care center, it was found that absolute majority of dental hygienists (93.4%) answered 'No' and only 6.6% dental hygienists answered 'Yes.' The standardized professional education are thought to be needed to be developed aiming at the success in oral-hygiene service within a LSCI, by strengthening professionalism in dental hygienists. 본 연구는 노인장기요양보험제도의 방문간호 중에서 치과위생사의 업무인 방문구강위생이 포함되어있으므로 치과위생사의 인지도를 파악하고자 2009년 1월부터 4월까지지 서울특별시, 인천광역시, 경기도의 치과병 의원에서 근무하는 치과위생사 259명을 대상으로 설문조사를 실시하였으며, 주요한 연구 결과는 다음과 같다. 1. 노인장기요양보험제도에서 치과위생사의 방문구강위생업무 중 중요한 업무순위에 대해 1순위가 '관리적, 예방적 처치 영역', 2순위는 '구강보건교육 영역'으로 나타났다. 구강보건교육 영역 중에서 중요한 교육분야는 '잇솔질'이 79.9%로 현저히 높게 나타났으며, 예방적 처치 영역 중에서도 '잇솔질 실행'이 64.5%로 가장 높게 나타났다. 2. 치과위생사가 방문구강위생업무를 하기위해 치과의사의 지시서가 필요한 것에 대한 인지여부에서 38.2%가 '예', 61.8%가 '아니오'라고 응답하였다. '예'라고 응답한 치과위생사 중 근무경력이 '1년 이상-4년 미만'인 치과위생사가 치과의사의 지시서 필요에 대해 인지하고 있는 비율이 13.9%로 가장 높게 나타났다(p<0.05). 3. 치과위생사가 노인장기요양소를 개설할 수 있는 것을 인지하고 있는 지에 대해 93.4%가 '아니오', 6.6%가 '예'라고 응답하였다. 학력에 따른 노인장기요양소 개설의향정도는 치과위생사의 학력이 '학사'인 경우가 3.48로 가장 높게 나타났다(p<0.001). 4. 노인장기요양보험제도의 인지정도에 대한 변수 중 '방문구강위생업무 시 치과의사의 지시서가 필요한 것에 대한 인지정도'와 '노인장기요양소 개설의향정도'와의 관계에서 음(-)의 상관관계(r=-0.300)를 보여주고 있으며, 통계적으로 유의한 차이를 보였다(p<0.01). 이상의 결과로 보아 노인장기요양보험제도의 수급자에게 구강위생업무를 제공해야할 치과위생사의 인지도가 낮으므로 노인장기요양보험제도에 대하여 치과위생사들에게 적극적인 홍보와 정기적인 교육을 통하여 인지도를 높여가야 할 것으로 사료된다.